Coping Self‐Efficacy Moderates the Association Between Severity of Partner Violence and PTSD Symptoms Among Incarcerated Women. Issue 5 (14th September 2015) - DeCou, Christopher R.; Lynch, Shannon M.; Cole, Trevor T.; Kaplan, Stephanie P.
Abstract: Previous research indicates self‐efficacy may function as a protective factor for survivors of partner violence (PV), including coping self‐efficacy specific to domestic violence. We hypothesized that domestic violence coping self‐efficacy would moderate the association between recent PV and posttraumatic stress disorder (PTSD) symptoms in a sample of incarcerated women, such that the association between PV and PTSD would be strongest at low levels of domestic violence coping self‐efficacy. Participants ( N = 102) were incarcerated women who reported PV in the year prior to incarceration. They were aged 19–55 years ( M = 33.57, SD = 9.32), identified predominantly as European American (84.3%), American Indian (15.7%), and Hispanic (14.7%), with 80.4% completing high school or more in terms of education. Participants responded to self‐report measures of PV, trauma history, domestic violence coping self‐efficacy, and current PTSD symptoms. In a series of sequential regression analyses, PV (β = .65, sr 2 = .06, p = .017) was significantly associated with current PTSD symptoms above and beyond past trauma history (β = .37, sr 2 = .14, p < .001), and this association was moderated by domestic violence coping self‐efficacy (Domestic Violence Coping Self‐Efficacy × Partner Violence; β = −.54, sr 2 = .03, p = .044). The relationship between PV and PTSD symptoms was greatest at low and average levels of domestic violence coping self‐efficacy and nonsignificant at high levels of domestic violence coping self‐efficacy. These findings highlight the importance of assessing domestic violence coping self‐efficacy in incarcerated women with recent PV, given that domestic violence coping self‐efficacy appeared to be protective against symptoms of PTSD.